Phenotypic plasticity in trait performance of common dairy goat breeds under diverse environments: a systematic review - Mashamaite, Puleng Kgabo; Tada, Obert (Frontiers in Animal Science, 2025)
IntroductionDairy goat genotypes thrive across a range of ecological systems, making phenotypic plasticity highly relevant under constant environmental fluctuations. Maintaining production efficiency has become a priority for sustainable farming. The study explored existing literature on phenotypic plasticity of dairy goat breeds in response to varying environmental conditions across the world.MethodsPublication searches were conducted on Google Scholar, PubMed, ResearchGate, and ScienceDirect databases. Following the PRISMA guidelines, the systematic review explored articles published between 2004 and 2024 from thirty-three (33) studies.ResultsThese studies extend across various agro-ecological zones, highlighting differences in trait adaptability among breeds such as Alpine, Toggenburg, Saanen, and indigenous goats. The results showed high-yielding breeds performed optimally in temperate environments but struggled under heat stress, showing reduced milk yield and escalated reproductive inefficiencies. Conversely, indigenous breeds demonstrated superior phenotypic plasticity, maintaining consistent growth and reproductive performance in tropical and semi-arid zones.DiscussionThese findings emphasize the importance of breed selection for environmental adaptability to sustain productivity in dairy goat farming. This review addresses phenotypic plasticity and trait variability in dairy goat breeds across diverse environments, with an emphasis on environmental adaptability and genotype-by-environment interactions.